Pengaruh Kompetensi Manajerial Kepala Sekolah, Komitmen Guru dan Peran Komite Sekolah terhadap Peningkatan Mutu Pendidikan di Sekolah Dasar Negeri - Sari, Denni Puspita; Juliejantiningsih, Yovitha; Maryanto, Maryanto (PGRI Kota Semarang, 2024)
Quality education is one of the main challenges faced by the education system in Indonesia, especially at the primary and secondary education levels. This research aims to examine the influence of the principal's managerial competence, teacher commitment, and the role of the school committee on the quality of education in public elementary schools in Randublatung District, Blora Regency. A quantitative approach with a descriptive correlational research design was used to evaluate the relationship between these variables. The population of this study consisted of 477 teachers from 52 state elementary schools. The research sample was taken as many as 218 teachers using the Slovin sampling technique with an error rate of 5%. The research instrument is a questionnaire that has been validated and its reliability tested, covering the variables of educational quality, managerial competence of the school principal, teacher commitment, and the role of the school committee. The results of data analysis show that there is a significant influence of the principal's managerial competence, teacher commitment, and the role of the school committee on the quality of education. These findings indicate that improving the quality of school management, teacher loyalty and professionalism, as well as the active involvement of school committees in the education process can improve the quality of education in elementary schools. This research contributes to the development of strategies for improving the quality of education in elementary schools, as well as providing a basis for education policies to strengthen the role of school principals, teachers and school committees in efforts to improve the quality of education.